A dynamic trust evolution model for MANETs based on mobility. (2018) - Reddy, Vijender Busi; Venkataraman, S.; Negi, Atul
Mobile ad-hoc networks (MANETs) are said to be open, anonymous, dynamic and mobile in nature which makes them vulnerable to several types of attacks. Mobility of a node is a source of vulnerability and raises challenges in setup and maintenance of secure and reliable communication. We propose here a trust model that enables a node in a network to assess confidence in its immediate and extended neighbourhood. We derive a trust parameter Mobility Factor to assess node's mobility. The effects of mobility are included as a parameter in the trust evaluation. Proposed trust assessment allows identification of node's capricious behaviour using the concept of trust flutter. A formal proof is presented here supports the adequacy of the proposed approach. ns-2 simulations with mobility and malicious nodes show better performance of proposed approach as compared to recent work (TSR (Lia et al., 2013)). Improved resilience against packet-dropping/modification attack and on-off attacks was observed.